Cholesterol footprint in high-resolution structures of serotonin receptors: Where are we now and what does it mean?. (September 2021) - Sarkar, Parijat; Chattopadhyay, Amitabha
Highlights: Serotonin receptors are a large family of receptors involved in regulating a wide array of physiological signaling pathways. A novel feature of many serotonin receptor structures is the presence of closely bound cholesterol molecules. The high-resolution cryo-EM structure of the apo -serotonin1A receptor harbors maximum number of bound cholesterol molecules. Serotonin1A receptor senses membrane cholesterol via a lysine residue in a CRAC motif in transmembrane helix 2. A combination of experimental and computational approaches could address the basis for cholesterol-sensitive GPCR function. Abstract: An emerging feature of several high-resolution GPCR structures is the presence of closely bound cholesterol molecules. In this Perspective, we share the excitement of the recent advancements in GPCR structural biology. We further highlight our laboratory's journey in comprehensively elucidating functional sensitivity of GPCRs (using the serotonin1A receptor as a representative neurotransmitter GPCR) to membrane cholesterol and validation using a variety of assays and molecular dynamics simulations. Although high-resolution structures of many GPCRs have been reported in the last few years, the structure of the serotoin1A receptor proved to be elusive for a long time. Very recently the cryo-EM structure of the serotoin1A receptor displaying 10 bound cholesterol molecules has been reported. We conclude by providing a critical analysis of caveats involved in GPCR structure determination.